2003
DOI: 10.1023/a:1023395409746
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Chrysosporium keratinophilum IMI 338142 isolated from a waste site containing organopollutants was studied for its ability to produce extracellular proteases on glucose-gelatin medium. Fungus was observed to be a potent producer of such enzymes. Enzyme secretion was best at 15 days of incubation period at pH 8 and temperature 40 degrees C. Asparagine was repressive to protease expression. No relationship existed between the enzyme yield and increase in biomass. Exogenous sugars suppressed enzyme production in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…strong mechanical destruction combined with lysis, produce the effect of keratinolysis (Kunert 2000; Mitola et al 2002). The reserve effect was noted in studies by Singh (2002) where a high activity of fungal keratinases was correlated with weak solubilization of keratin substrate. The authors attribute this to the removal or repression of some accessory proteins required by keratinase to act effectively on the keratin molecule while splitting its disulfide bonds.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…strong mechanical destruction combined with lysis, produce the effect of keratinolysis (Kunert 2000; Mitola et al 2002). The reserve effect was noted in studies by Singh (2002) where a high activity of fungal keratinases was correlated with weak solubilization of keratin substrate. The authors attribute this to the removal or repression of some accessory proteins required by keratinase to act effectively on the keratin molecule while splitting its disulfide bonds.…”
Section: Discussionmentioning
confidence: 84%
“…For those reasons the fungi constitute an important group among the destruents of organic matter in the soil and, as reported by Singh (2002), in the bioremediation of environments polluted with keratin waste. According to Vasileva-Tonkova et al (2009) and Syed et al (2009), microbiological degradation of keratin waste is also an ecologically and economically safe method of utilization of such waste.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…3.4.99.11), peptidases which are capable of degrading keratin. Various authors have reported that, among the keratinolytic microorganisms, some species of Bacillus [1012], actinomycetes [9, 13, 14], and fungi [1517] are able to produce these keratinases and peptidases. …”
Section: Introductionmentioning
confidence: 99%
“…Las queratinasas por su amplio espectro de acción tienen numerosas aplicaciones en diversas industrias: biomedicina, bioenergía, textil, medicina, cosmética, cuero, bioconversión de residuos queratínicos Singh, 2002).…”
Section: Aplicaciones Biotecnológicas De Las Queratinasasunclassified